Scaffolding to Support Better Achievement in Mathematics - Nila Mareta Murdiyani (PYTHAGORAS Jurnal Pendidikan Matematika, 2013)
According to the National Science Education Standards, teachers should emphasize students’ interests, needs, experiences, inquiry, collaboration and understanding in their classrooms. One of the characteristics of inquiry is using scaffolding. Because of the benefits, it is important to investigate the effect of scaffolding on achievement in mathematics. Based on some relevant previous studies, scaffolding can be used to support better achievement in mathematics. In scaffolding, teacher’s guidance decreases gradually and student’s autonomy increases gradually. By giving guidance, teacher revises student’s misconceptions; while by giving autonomy, teacher supports student’s motivation in learning. Minimizing misconceptions and maximizing motivation can lead students to better achievement in mathematics. Many studies in this paper emphasize the importance of teachers' contribution in giving scaffolding to their students. Further research should be conducted to investigate the role of other people surrounding the students, such as parent and peer, in supporting effective scaffolding.Keywords: scaffolding, achievement in mathematics, misconceptions, motivation